Opting for Elsewhere : Lifestyle Migration in the American Middle Class - Hoey, Brian A., 1968- (Book collections on Project MUSE., 2014)
""Opting for Elsewhere examines the stories of everyday Americans who move to new places as a way to redefine themselves through reordering work, family, and personal priorities. Their lifestyle migration expresses longstanding cultural values while also demonstrating developing responses to distinctive contemporary challenges and opportunities"--Provided by publisher"--